2014
DOI: 10.3855/jidc.3000
|View full text |Cite
|
Sign up to set email alerts
|

Shigellemia in a post renal transplant patient: a case report and literature review

Abstract: Shigellemia is a complication of shigellosis that occurs generally in malnourished children. In adults, shigellemia is usually seen in immunocompromised individuals. Here we report the first case of shigellemia in a renal transplant patient from India. The patient had history of diarrhea, which was treated symptomatically. Subsequently, the patient developed high-grade fever and blood culture was positive for Shigellaflexneri. Recovery was uneventful after the initiation of antimicrobial therapy. In a country … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…; Appannanavar et al . ). Shigella bacteraemia is mostly caused by S. dysenteriae type 1 and S. flexneri 3a followed by S. sonnei (Sharma and Arora ).…”
Section: Extraintestinal Complications Of Shigella Serotypesmentioning
confidence: 97%
See 2 more Smart Citations
“…; Appannanavar et al . ). Shigella bacteraemia is mostly caused by S. dysenteriae type 1 and S. flexneri 3a followed by S. sonnei (Sharma and Arora ).…”
Section: Extraintestinal Complications Of Shigella Serotypesmentioning
confidence: 97%
“…However, very few cases have been reported so far in India (Appannanavar et al . ). Shigella infection should be considered as a differential diagnosis when encountering severe sepsis associated with diarrhoea and vomiting in infants and young children.…”
Section: Extraintestinal Complications Of Shigella Serotypesmentioning
confidence: 97%
See 1 more Smart Citation
“…The common microbes implicated in these infections include Streptococcus pneumonia , Escherichia coli , Staphylococcus aureus , Staphylococcus epidermidis , Pseudomonas aeruginosa , and Candida albicans [ 7 ]. Shigella flexneri , Proteus vulgaris , Klebsiella pneumoniae , and Enterococcus faecalis lead to diabetes foot ulcer [ 8 11 ]. The bacteria associated with gastrointestinal and urinary tract infections include Klebsiella pneumoniae , Streptococcus pyogenes , and Serratia marcescens [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Morduchowicz et al reported 27 cases of Shigella bacteremia of which 16 had an underlying predisposing condition [12]. Appannanavar et al also reported a case of bacteremia in a renal transplant patient and two other cases in postrenal transplant are reported in literature [8, 25, 26]. Hawkins et al presented a total of 9 cases of Shigella bacteremia in adults with underlying predisposing comorbidities including the use of immunosuppressant, diabetes mellitus, alcohol liver disease, HIV/AIDS, and malignancy [16].…”
Section: Discussionmentioning
confidence: 99%